2017
DOI: 10.1084/jem.20161645
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory signals from photoreceptor modulate pathological retinal angiogenesis via c-Fos

Abstract: Pathological neovessels growing into the normally avascular photoreceptors cause vision loss in many eye diseases. Sun et al. find that a master inflammatory regulator, c-Fos, in photoreceptor controls retinal blood vessel growth into the photoreceptors through the inflammatory signal–induced STAT3/VEGFA pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 66 publications
3
74
0
2
Order By: Relevance
“…Moreover, mice with Vldlr deficiency developed other pathologic features of wet AMD, such as degeneration of rod and cone photoreceptors and chronic inflammation in the retina and RPE (113,114). The unique pathological features in this mouse model enabled numerous studies that investigated the potential mechanisms and treatments of AMD, RAP, and macular telangiectasia, including antioxidants, neurotrophic factors, resveratrol, anti-inflammation, cellular bioenergetics, and transcriptional control (112,(114)(115)(116)(117)(118)(119), where dietary treatments with either antioxidants or resveratrol were demonstrated to be effective therapies to suppress Vldlr 2/2 neovascularization.…”
Section: Vldlr Germline-knockout Micementioning
confidence: 99%
“…Moreover, mice with Vldlr deficiency developed other pathologic features of wet AMD, such as degeneration of rod and cone photoreceptors and chronic inflammation in the retina and RPE (113,114). The unique pathological features in this mouse model enabled numerous studies that investigated the potential mechanisms and treatments of AMD, RAP, and macular telangiectasia, including antioxidants, neurotrophic factors, resveratrol, anti-inflammation, cellular bioenergetics, and transcriptional control (112,(114)(115)(116)(117)(118)(119), where dietary treatments with either antioxidants or resveratrol were demonstrated to be effective therapies to suppress Vldlr 2/2 neovascularization.…”
Section: Vldlr Germline-knockout Micementioning
confidence: 99%
“…Dietary modulation of the lipid supply can positively influence diseases with pathological neovascularization such as ROP, AMD, and DR in patients and in animal models of retinopathy (Gong et al , ). Photoreceptor energy demands drive vessel growth (Sapieha, ; Joyal et al , , ; Fu et al , ), while photoreceptor‐derived oxidative stress and inflammation lead to retinal vascular damage or regression (Kern & Berkowitz, ; Sun et al , ). Retinal disorders such as ROP, DR, AMD, RP, and Zellweger spectrum disorder (ZSSD) are associated with disturbances in photoreceptor activity, which may further affect the blood supply and induce pathological vascular remodeling during disease progression.…”
Section: Dyslipidemia In Neurovascular Retinopathiesmentioning
confidence: 99%
“…Chronic inflammation may induce AMD by stimulating the formation of an abnormal vessel structure. Hemamoeba was discovered in choroiditis in the eyes of AMD patients (7). It was identified that auto-antibodies to attack vitreous bodies, retinal pigment epithelium and retinal tissue in AMD patients (11).…”
Section: Role Of Inflammatory Factors In the Effects Of Aflibercept Omentioning
confidence: 99%
“…However, vascular endothelial growth factor A (VEGF-A), a cytokine that promotes angiogenesis and vascular permeability, is one of the most important factors that promotes neovascularization (6). Active forms of VEGF-A have been identified in CNV (7)(8)(9). Anti-VEGF therapies are now becoming the focus of AMD treatment (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation